Bio-waste Corn-cob Cellulose Supported Poly(hydroxamic acid) Copper Complex for Huisgen Reaction: Waste to Wealth Approach - Mandal, Bablu Hira; Lutfor, M. R.; M. M., Yusoff; K. F., Chong; Sarkar, Shaheen M. (Elsevier Ltd, 2017)
Corn-cob cellulose supported poly(hydroxamic acid) Cu(II) complex was prepared by the surface modification of waste corn-cob cellulose through graft copolymerization and subsequent hydroximation. The complex was characterized by IR, UV, FESEM, TEM, XPS, EDX and ICP-AES analyses. The complex has been found to be an efficient catalyst for 1,3-dipolar Huisgen cycloaddition (CuAAC) of aryl/alkyl azides with a variety of alkynes as well as one-pot three-components reaction in the presence of sodium ascorbate to give the corresponding cycloaddition products in up to 96% yield and high turn over number (TON 18,600) and turn over frequency (TOF 930 h−1) were achieved. The complex was easy to recover from the reaction mixture and reused six times without significant loss of its catalytic activity.